2014
DOI: 10.3390/ijerph111212190
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Acute Respiratory Infections and Household Environment in an Eastern Indonesian Urban Setting

Abstract: This pilot study evaluated the potential effect of household environmental factors such as income, maternal characteristics, and indoor air pollution on children’s respiratory status in an Eastern Indonesian community. Household data were collected from cross-sectional (n = 461 participants) and preliminary childhood case-control surveys (pneumonia cases = 31 diagnosed within three months at a local health clinic; controls = 30). Particulate matter (PM2.5 and PM10) was measured in living rooms, kitchens, child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 27 publications
5
45
0
2
Order By: Relevance
“…A high incidence of pneumonia (0.27 episodes per child-year (95% CI 0.23–0.32)) was reported in infants in the Drakenstein Child Health study, an African birth cohort study; maternal smoking was strongly associated with pneumonia (OR 2.36, 95% CI 1.45–3.82) [39]. Studies from Nepal and Indonesia confirm a similar risk [40,41], and in a large questionnaire-based study from Taiwan, prenatal ETS exposure or maternal smoking were significant risk factors for infantile pneumonia [42]. A Vietnamese study of almost 25,000 children less than 5 years of age found that household ETS exposure to be independently associated with hospitalization for pneumonia (adjusted OR 1.55, 95% CI 1.25–1.92) [43].…”
Section: Resultsmentioning
confidence: 87%
“…A high incidence of pneumonia (0.27 episodes per child-year (95% CI 0.23–0.32)) was reported in infants in the Drakenstein Child Health study, an African birth cohort study; maternal smoking was strongly associated with pneumonia (OR 2.36, 95% CI 1.45–3.82) [39]. Studies from Nepal and Indonesia confirm a similar risk [40,41], and in a large questionnaire-based study from Taiwan, prenatal ETS exposure or maternal smoking were significant risk factors for infantile pneumonia [42]. A Vietnamese study of almost 25,000 children less than 5 years of age found that household ETS exposure to be independently associated with hospitalization for pneumonia (adjusted OR 1.55, 95% CI 1.25–1.92) [43].…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, burning household solid waste emanates many harmful particulates which pollutes the air (Gullett et al, 2010;Hoornweg, D., & Bhada-Tata, 2012;Li, Lei, Bei, & Molina, 2012;Ochoa et al, 2012;Vergara & Tchobanoglous, 2012). Many studies have shown evidence on the deleterious health effects of the pollution emanated from burning solid waste on morbidity and mortality (Burnley, 2014;Kodros, Wiedinmyer, Ford, Cucinotta, & Gan, 2016;Lelieveld, Evans, Fnais, Giannadaki, & Pozzer, 2015;Schwartz, Bind, & Koutrakis, 2017;Shibata, Wilson, Watson, Leduc, & Meng, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the scale of the health effects of burning household solid waste in the open could be massive given the fact that Indonesia is the fourth most populated country in the world, with population over 255 million in 2015 based on the latest Intercensal Population Census (Badan Pusat Statistik, 2016) What is worrying is that exposure to particulate matter (PM), one of the pollutants resulted from burning solid waste, adversely affect the respiratory health of children (Shibata et al, 2014). Given the issues above, it is interesting and imperative to know whether exposure to pollution from burning household solid waste in the open affect respiratory health of children.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, pneumonia accounts for 15% of all deaths in children less than 5 years of age and was the largest infectious cause of death in children in 2015 (Shibata et al, 2014). Many studies have demonstrated associations between selected air pollutants and adverse health effects in children in the aspects of childhood hospital admissions (Barnett et al, 2005), school absences (Hales et al, 2016), physician visits for upper and lower respiratory illness (Aguilera et al, 2005), and deficits in lung function growth rates (den Dekker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%